Polygraph screening in the South African workplace: veracity verification or victimisation? - Herbig, Friedo Johann Willem (Acta criminologica, 2018)
Pervasive and suffocating corruption and dishonesty have become commonplace in South African society. Determining the integrity of employees, both prospective and existing, in the workplace is of cardinal importance for business owners, managers and human resource practitioners alike in order to optimally administer human capital/industrial relations, and to protect their assets and the reputation of their enterprises. To this end polygraph examinations are frequently employed in South African corporate society to facilitate, amongst others, job applicant vetting, routine staff integrity screening and/or the testing of employees suspected of being involved in workplace infidelity. Unsurprisingly, polygraph testing has generated considerable scientific and public controversy. Lie detector tests, as they are commonly referred to in colloquial speech, have become a popular cultural icon — from crime dramas to comedies to advertisements — the portrayal of a polygraph stylus agitating on a moving chart is a readily recognised symbol. As the application of polygraph techniques grow in public visibility and use in corporate society, specifically as an investigatory mechanism, the vexing question is whether the polygraph, when applied in a workplace setting for specifically personnel screening, has the potential to victimise employees (candidate or existing)? This article, instead of rigidly focusing on validity and accuracy issues of the polygraph examination per se, examines certain utilitarian issues relating to this question from a metaphysical and discursive standpoint. Such focus seeks to reveal areas where potential prejudice, harassment or victimisation of aspiring and current employees exists. The incremental value hereof could well expose the potential victimisation impact of polygraph application during personnel vetting and retention exercises and is intended to serve as a caveat regarding the unmitigated usage of polygraph. This article, therefore, seeks to apprise the more obscure and undervalued dynamics underlying screening tests leading to a better understanding of the conundrum that presents in this arena and ultimately serving as a caution against grasping for overzealous cures.